Effectiveness of applying the structure and content of the information component in the technical and tactical training of libero players - Filimonov, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and experimentally prove the effectiveness of applying the structure and content of the information component in the technical and tactical training of libero players. Methods and structure of the study. The pedagogical experiment was conducted with libero players participating in the Moscow Student Sports Games in volleyball 2023/2024. The qualification of the players ranged from Category I to Candidate for Master of Sport. 12 athletes took part in the experiment, who were divided into two groups – control (CG) and experimental (EG) – of 6 people each. The CG trained on the basis of the sports training programme for the sport of “volleyball” (2), while a methodology based on the identification of visual-informational images and signs in the actions of the opponent’s attacking team, as well as the identification of trigger mechanisms of the libero’s responsive actions, was introduced into the training process of the EG. Tests on physical and technical-tactical preparedness were conducted. Results and conclusions. On the basis of the conducted research, the structure and content of the information component, preliminary and control testing of the physical and technical-tactical preparedness of libero players was carried out.